A prospective randomized controlled study comparing patient-reported scar evaluation of single-port versus multiport laparoscopic appendectomy for acute appendicitis - Kyeong Eui Kim; In Soo Cho; Sung Uk Bae; Woon Kyung Jeong; Hyung Jin Kim; Seong Kyu Baek (Journal of Minimally Invasive Surgery, 2023)
Purpose: This study aimed to compare the postoperative outcomes and patient-surveyed scar assessments of single-port laparoscopic appendectomy (SPLA) with the outcomes of multiport laparoscopic appendectomy (MPLA). Methods : Between August 2014 and November 2017, the prospective randomized study comprised 98 patients diagnosed with acute appendicitis and indicated for surgery. Fifty-one patients had MPLA and 47 patients received SPLA. The primary endpoint was the total score of Patient Scar Assessment Questionnaire (PSAQ) administered to patients 6 weeks after surgery. Results : SPLA involved a shorter median operative time than MPLA (47.5 minutes vs. 60.0 minutes, p = 0.02). There were no apparent differences in the time before diet tolerance, length of hospital stay, and postoperative complication. SPLA patients had shorter total incision length (2.0 cm vs. 2.5 cm, p < 0.01) and required fewer analgesics on the day of surgery than MPLA patients (p = 0.011). The PSAQ favored the SPLA approach, revealing significant differences in total score (48 vs. 55, p = 0.026), appearance (15 vs. 18, p = 0.002), and consciousness (8 vs. 10, p = 0.005), while satisfaction with appearance and symptoms scale did not (p = 0.162 and p = 0.690, respectively). Conclusion : The postoperative scar evaluated by the patient was better with SPLA than with MPLA, and patient satisfaction with the scar was comparable between the two techniques.